Urban green areas as earthworm species maintainers in Curitiba, Paraná, Brazil - Dudas, Rafaela T.; Tavares, Alan A. T.; Ercole, Caique; de Lara, Brunna L.; Carlos, Esthefany Da S.; Torres, Julia L. M.; Smokanit, Manoela; Guaranha, Raquel M.; Brown, George G.; Bartz, Marie L.c (Zootaxa, 2023)
Urban green areas can have a high impact on soil fauna due the environmental changes caused by human activities. This work aimed to assess earthworm populations in urban sites in the city of Curitiba, Paraná, Brazil. Earthworms were sampled in two urban sites: the Campus Ecoville of the Universidade Positivo and the Casa Verde space and in two land use systems (Grass Lawn and Native Vegetation), in the summer of 2018 and 2019 and winter of 2019. A total of 1052 individuals were found, belonging to five families and 12 species were identified, of which five are native: Glossoscolex sp.55, Fimoscolex sp.36, Fimoscolex sp.37 (Glossoscolecidae), Andiorrhinus duseni (Rhinodrilidae) and Ocnerodrilidae sp.43 (Ocnerodrilidae) and seven are exotic species: Amynthas corticis, Amynthas morrisi, Metaphire californica, Metaphire schmardae (Megascolecidae), Dendrodrilus rubidus (Lumbricidae) and Pontoscolex corethrurus (Rhinodrilidae). Of the five native species found, four are new species and will be described in the future and the specie A. duseni belongs to the group known as giant earthworms (minhocuçu) with specimens larger than 30cm. Despite the predominance of exotic species (n=932) compared to native species (n=114), the presence of new species may indicate that the managed environments can preserve native species. Moreover, the difference in the total number (native vs. exotic) can be attributed to the ability of the exotic species to survive human disturbances.